‘This won’t hurt a bit!’ – A descriptive review of health care professionals’ pharmacological management of pain in minor trauma - Duncan M. Havenga; Jaykumaran Govender; Carolyn Lewis (South African Family Practice)
Background: Emergency Centres (ECs) have a prominent trauma burden requiring effective pain management. This study aimed to review analgesia-prescribing habits in minor trauma, reviewing the patient demographics and diagnoses, analgesia-prescribing habits of health care professionals (HCPs) managing these cases, and differences in prescribing noted by patients’ age group, gender and triage code.